2022
DOI: 10.1088/1402-4896/ac7c97
|View full text |Cite
|
Sign up to set email alerts
|

Dual dielectric grating-assisted enhancement of Goos-Hänchen shift in monolayer graphene

Abstract: Recently, the dielectric gratings have been used in enhancing the Goos-Hänchen (GH) shifts of monolayer graphene. However, many of these structures are limited within single dielectric grating. Dual dielectric gratings are compelling candidates for the manipulation of the light-matter interaction owing to their flexible degree of freedom in geometrical parameters. Here, we present the GH shift of the reflected wave in the dual dielectric grating layers by using rigorous coupled-wave analysis (RCWA) and station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Therefore, some simulations are based on a plane wave. Ma et al presented the GH shift of reflected wave in the dual dielectric grating layer, with the GH shift being more than 8000 times the incident wavelength, and the reflection of only 0.0022 [20]. Zhu et al demonstrated that the asymmetric grating with monolayer MoS 2 had achieved a GH shift as high as 9490λ, with a reflection of only 0.018 [21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some simulations are based on a plane wave. Ma et al presented the GH shift of reflected wave in the dual dielectric grating layer, with the GH shift being more than 8000 times the incident wavelength, and the reflection of only 0.0022 [20]. Zhu et al demonstrated that the asymmetric grating with monolayer MoS 2 had achieved a GH shift as high as 9490λ, with a reflection of only 0.018 [21].…”
Section: Introductionmentioning
confidence: 99%